Estudios andrológicos básicos como apoyo para el examen de toros criollos (2013)
Andrological studies add important for reproductive examination of bulls that are used in natural mating in large areas of tropical savanna. In the present paper is a review comparison of methods for dilution and freezing of bovine semen. It discusses the experience of a work in floodplain, and are some environmental factors affecting type the value of mobility of bovine semen.It is concluded that more studies should be made to analyze the behavior of the semen when it shows good results in the freezing process.